Ultrathin FeTe nanosheets with tetragonal and hexagonal phases synthesized by chemical vapor deposition. (May 2021) - Wang, Xingguo; Bian, Ce; He, Yixiang; Guo, Jie; Zhang, Peng; Liu, Lixuan; Wei, Yi; Meng, Lingjia; Jiang, Huaning; Li, Bixuan; Nie, Anmin; Bao, Lihong; et al.
Graphical abstract: Abstract: 2D functional materials, such as 2D magnet and superconductor, spark massive interests from synthesis, manipulation to application. Especially, FeTex with multi-phases provides an ideal platform to explore the possible superconducting, ferromagnetic or antiferromagnetic properties and even their functional heterostructures. Herein, we report a facile chemical vapor deposition (CVD) approach to synthesize ultrathin tetragonal FeTe (down to monolayer), hexagonal FeTe (down to 2.3 nm), and Fe-rich hexagonal FeTe with superlattice by tuning the growth temperature according to the phase diagram. Scanning transmission electron microscopy (STEM) is further performed to confirm the difference among these various FeTe phases. Magneto-transport illustrates that the tetragonal device displays a high linear magnetoresistance (LMR) up to 10.5% at 1.9 K, and the LMR of hexagonal FeTe reaches 5.8% at 1.9 K. Interestingly, O doped tetragonal thick FeTe displays a superconducting transition at 9 K, which can persist even at 16 T. In summary, this study illustrates a phase-selective synthesis of FeTex ultrathin crystals, providing promising opportunities to construct complicated devices such as ferromagnet/antiferromagnet, magnet/superconductor heterostructures.